Effective management in digital era labor sphere in university graduates view: Possible transformations and problems - Nevolina, Victoria V.; Prokhodtsev, Kirill A.; Osipova, Natalia V.; Zharkova, Alena A.; Karpenko, Galina V.; Volkova, Victoria B.; Yudina, Anna M. (Linguistics and Culture Review, 2021)
The article analyzes the mutual ideas of university graduates and employers as the main entities of social and labor relations about effective management in the organization. As a research method, the questionnaire method was used, which allows quick and effective investigating of university graduates’ ideas about management in the labor sphere. The authors of the article analyzed the similarities and discrepancies in the views of the labor relations parties from each other and the real actions of the opposite party. The article considers the structure of the basic ideas about the effectiveness of management in the labor sphere. It is determined that on the part of university graduates, the following are important: job security, timely payment of wages, financial assistance to employees in need, good relations with superiors. It is revealed that on the part of employers, it is important to: fulfill one's official duties, keep to discipline, and make trusting relationships. The main discrepancy in the views of university graduates and employers is observed in the understanding of preferential seniority, which gives various privileges to the employee.